Sistem Pendukung Keputusan Penghitung Kalori Diet bagi Diabetesi - Feryani Aldyningtys; Tito Pinandita; Harjono Harjono (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2012)
Setting up a diet for diabetics is highly recommended, because diabetes disease occurs because of unbalance metabolism on the sufferer. Setting the food intake of calorie consumption is needed as a way to maintain the stability of blood sugar in patients. This decision support system is based on the formula for calculating the calories of ordinary doctors and nutritionists use to determine a diet for diabetics in accordance with its weight. The result of this calculation is a basal calories which will then return the total calories with correction in accordance with the state of the patient, which is then divided again into the intakes of calories per consumption time such as for breakfast, lunch, dinner and snack. The purpose of the division so that a diet made by diabetic patients can achieve maximum results